PERBEDAAN WAKTU CLEARANCE IMPOR SEBELUM DAN SESUDAH IMPLEMENTASI PUSAT LOGISTIK BERIKAT (PLB) - Raden Didiet Rahmat Hidayat; Mohammad Iqbal Firdaus; Lis Lesmini; Endang Sugiharti; Latifah Dwi Handayani (Jurnal Logistik Indonesia, 2018)
Pusat Logistik Berikat (PLB) or The Bonded Logistics Center is part of the Government's Economic Policy Package issued in September 2015. This clarified by Regulation of the Minister of Finance No. 272 of 2015 on Bonded Logistics Center (PLB) plus the Regulation of the Director General of Customs and Excise No. 1 of 2016, Regulation of the Director General of Customs and Excise No. 2 of 2016 and Regulation of the Director General of Customs and Excise No. 3 of 2016.  The Implementation of Bonded Logistics Center (PLB) has managed to reduce the clearance time process from 4 days to 1.8 days.